Magnetospheric Ion Evolution Across the Low‐Latitude Boundary Layer Separatrix. Issue 10 (19th October 2017) - Vines, S. K.; Fuselier, S. A.; Trattner, K. J.; Burch, J. L.; Allen, R. C.; Petrinec, S. M.; Anderson, B. J.; Webster, J. M.; Ergun, R. E.; Giles, B. L.; Lindqvist, P.‐A.; Russell, C. T.
Abstract: On 20 September 2015, the Magnetospheric Multiscale (MMS) spacecraft crossed the dusk magnetopause after a compression of the magnetosphere. Enhanced densities and fluxes of both colder (≤10 eV) and hotter (>1 keV) magnetospheric and magnetosheath heavy ion species were observed reaching the magnetopause. The evolution of the velocity distributions for H +, He +, and O + measured by the Hot Plasma Composition Analyzer on MMS during this magnetopause crossing is presented. In particular, this study focuses on the changes in the species' distribution functions as MMS passes from the magnetosphere through the electron edge of the low‐latitude boundary layer (LLBL) separatrix and then into the LLBL. Two types of processes are suggested to play a role in the heating of colder magnetospheric ions across the LLBL separatrix in the region between the separatrix and the electron and ion edges of the LLBL. One mechanism leads to the formation and enhancement of ring distributions in this layer of the LLBL as the magnetospheric ions propagate across the separatrix. A second mechanism leading first to perpendicular heating and then to parallel heating of colder protons may arise from a possible two‐stream instability as the magnetospheric ions first encounter the warmer magnetosheath electrons in the electron layer and then the warmer magnetosheath ions between the electron and ion edges of the LLBL separatrix. Perpendicular heating of He + and O + is seen more so in the main reconnection exhaust, due to nonadiabatic behavior of these ions as they are accelerated up to the bulk flow speed. Key Points: Evolution of magnetospheric H +, He +, and O + distributions from MMS‐HPCA tracked during magnetopause crossing Initial heating of cold H + likely from MTSI across the LLBL separatrix, while He + and O + perpendicular ring distributions mainly enhanced He + and O + accelerated nonadiabatically in exhaust, and magnetospheric ions are seen to reflect off of the magnetopause current layer